2019
DOI: 10.1161/atvbaha.118.312233
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Flow Increases UBE2C (Ubiquitin E2 Ligase C) via Loss of miR-483-3p, Inducing Aortic Valve Calcification by the pVHL (von Hippel-Lindau Protein) and HIF-1α (Hypoxia-Inducible Factor-1α) Pathway in Endothelial Cells

Abstract: Objective— Calcific aortic valve (AV) disease, characterized by AV sclerosis and calcification, is a major cause of death in the aging population; however, there are no effective medical therapies other than valve replacement. AV calcification preferentially occurs on the fibrosa side, exposed to disturbed flow (d-flow), whereas the ventricularis side exposed to predominantly stable flow remains protected by unclear mechanisms. Here, we tested the role of novel flow-sensitive UBE2C (ubiquitin E2 li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 72 publications
2
47
0
Order By: Relevance
“…These studies revealed that HIF-1α can be activated by disturbed blood flow in vivo. In addition, these studies, using in vitro flow systems that recapitulate the shear stress in vivo, show that endothelial cells exposed to disturbed flow under normoxic conditions had elevated HIF-1α mRNA and protein levels [9,11,96]. Thus, it appears from these findings that both hypoxia induced by disturbed flow, and disturbed flow itself can induce HIF-1α expression.…”
Section: Disturbed Flow Activates Hif-1αmentioning
confidence: 86%
See 2 more Smart Citations
“…These studies revealed that HIF-1α can be activated by disturbed blood flow in vivo. In addition, these studies, using in vitro flow systems that recapitulate the shear stress in vivo, show that endothelial cells exposed to disturbed flow under normoxic conditions had elevated HIF-1α mRNA and protein levels [9,11,96]. Thus, it appears from these findings that both hypoxia induced by disturbed flow, and disturbed flow itself can induce HIF-1α expression.…”
Section: Disturbed Flow Activates Hif-1αmentioning
confidence: 86%
“…Consistent with this, Feng et al [9] show that HIF-1α was also elevated at sites of disturbed flow in porcine and murine arteries. A study by Fernandez Esmerats et al [96] shows that HIF-1α was enhanced in endothelial cells exposed to disturbed flow located at the fibrosa Figure 4. Outline of simplified mass transport considerations for oxygen transport to a blood vessel wall.…”
Section: Disturbed Flow Activates Hif-1αmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, more than one hundred genes have been identified to be governed by mammalian HIF during O 2 deprivation [42,43]. The involvement of HIF-1α in diseases of the vascular wall, including atherosclerosis, carotid stenosis, and aneurysms, has recently been proposed [44][45][46][47][48][49]. Indeed, insufficient expression of HIF is associated with CVD [50,51].…”
Section: Hypoxia-inducible Factorsmentioning
confidence: 99%
“…The expression of CDCA5 was reported to be closely linked to microvascular invasion and tumor diameter, and inhibition of CDCA5 expression impeded hepatoma cell proliferation and induced apoptosis (37). UBE2C was indicated to be highly expressed in HCC tumor tissues and patients with upregulated UBE2C were more likely to have higher-grade tumors and poor prognosis (38,39). Overexpression of MELK leads to cell cycle-and mitosis-associated gene expression, which influences cell division.…”
Section: Discussionmentioning
confidence: 99%